The work of Bahraini woman in international public relations and diplomatic protocol sector: Opportunities & Challenges - Al- Saqer, Layla Hassan (Journal of Humanities & Social Sciences, 2019)
This research aims to achieve an analytical study on the experience of Bahraini women in the international public relations and protocol sector. The research raises several questions regarding the experience of Bahraini women in this field and the opportunities and challenges facing the work of Bahraini women. This study uses both qualitative and quantitative approaches in analyzing the experience of Bahraini women in the international public relations and protocol sector, an area that has not been addressed in previous research. This research aims to fill the gap in the Arab Gulf research by analyzing the experience of Bahraini women in the international public relations and protocol sector through distributing a questionnaire to a purposive sample consisting of 100 male and female workers in the departments of international public relations and protocol with a response rate of 53%.  In addition, the researcher conducted open interviews with a purposeful sample of 12 female employees in senior and middle management positions in international public relations departments and ceremonies in government institutions in the Kingdom of Bahrain using the snowball sample. The research finds that 50% of the respondents indicated that there are no clear roles for women's work in the protocol sector in Bahrain, and 26% of respondents said that they do not know. Besides, 62.3% of respondents considered the importance of combining practical skills and academic qualifications when working in the protocol sector. Moreover, 25.5% of the respondents believe that Bahraini culture has an impact on the work of Bahraini women in the protocol sector, while 33.3% of the respondents believe that Bahraini culture has some impact on the work of Bahraini women in the protocol sector. While 79.2% of the respondents believe that there is no difference between women and men in the opportunities they have achieved in the international public relations and protocol sector, and 70.7% of the respondents believe that gender has not affected the challenges facing the workers in the protocol sector. Furthermore, the study found that Bahraini women have promising opportunities to develop their work in the international public relations and protocol sector because of the great support women receive from the Supreme Council for Women, led by Her Royal Highness Princess Sheikha Sabeeka bint Ibrahim Al Khalifa, the wife of the King of Bahrain, and the high percentage of women education and specialization in communication and media sciences. The study highlighted the major societal, institutional and personal challenges facing Bahraini women in the international public relations and protocol departments. The study recommends strengthening the role of institutions and media in promoting a new community culture that emphasizes the growing role of women in international public relations and ceremonies, in addition to encouraging and supporting research in this sector.
Keywords: Bahraini women; international public relations; diplomacy; ceremonies